CapCut Application Model to Boost User Interest in Vehicle Rental Promotions - Muhammad Z. Amany; Syarif Hidayat (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
In the current digital era, social media platforms such as TikTok and Instagram Reels play a crucial role in influencing consumer decisions. This abstract presents a model for leveraging the CapCut application to enhance user interest in car rental promotions through creative video content. The model focuses on producing engaging promotional videos that showcase various cars in captivating contexts, such as casual trips, city adventures, and special events. By utilizing the editing features available in CapCut, users can generate high-quality videos that highlight the benefits of car rental services, including flexibility, affordability, and unique experiences. The study's findings indicate that employing the CapCut application in creating car rental promotional content can significantly boost engagement levels. Creatively edited videos capture users' attention, with an average increase in interactions (likes, shares, comments) of 90% compared to unedited content.